L’artrodesi circonferenziale selettiva mini-invasiva nel trattamento della patologia discale degenerativa lombare - Piazzolla, A.; Bizzoca, D.; Montemurro, V.; Parato, C.; La Malfa, M.; Moretti, B. (Lo Scalpello - Journal, 2019)
MINIMALLY INVASIVE CIRCUMFERENTIAL FUSION IN LUMBAR DEGENERATIVE DISC DISEASEDegenerative lumbar spine disease is one of the leading causes of disability worldwide. Lumbar interbody fusion (LIF)is a valid approach in the treatment of several segmental spine pathologies, including degenerative disc disease. LIFmay be performed through open and minimally invasive procedures. This review aims to assess the state of the art inthe field of minimally invasive spine surgery in the treatment of degenerative disc disease.